From Jane Austen to Joseph Conrad : essays collected in memory of James T. Hillhouse - Rathburn, Robert Charles (University of Minnesota Press, 1958)
David Daisches, Douglas Bush, Robert B. Heilman, Arthur Mizener, and William Van P?Connor are among the contributors to this volume of essays on the nineteenth-century British novel. Each of the selections has been written expressly for this book and is p.